HARDNESS PHENOMENON IN BEACH PEA (Lethyrus maritimus L.) - U.D. Chavan; R. Amarowicz; F. Shahidi (Indonesian Agency for Agricultural Research and Development, 2013)
Beach pea is mostly grown on seashores and it contains higher amount of protein than other legumes. However, the pea has several undesirable attributes, such as long cooking time and hard to germinate (imbibitions) that limited its use as food. The present investigation aimed to study the physico-chemical properties, cooking characteristics and hull crude fibre structure of beach pea as compare to other similar legumes. Standard methods of processing pulses were used for present study. Beach pea seeds contained very low grain weight, density, hydration capacity, hydration index, swelling capacity and swelling index than the green pea and field pea. Beach pea had higher amount of crude protein, ash, crude fibre and polyphenols, but lower in starch content than the green pea and field pea. Without any treatment to beach pea seeds the water uptake capacity was very low. Mechanical treatment to beach pea seeds increasedthe water uptake percentage. The recovery of hull was 3 to 6 times higher in beach pea than that of green pea and field pea. The crude protein content in beach pea hull was 2-5% higher than others. The beach pea hull, dhal and whole seeds were good source of macro- and micro- minerals than that of the other two peas. The electron microscopic structure of beach pea hull crude fibre showed a very close and compact structure than green pea and field pea hull crude fibre structure. Lowering the hardness of beach pea seeds with mechanical or chemical treatments will give more scope for their utilization in the human nutrition.